2007
DOI: 10.1038/sj.emboj.7601754
|View full text |Cite
|
Sign up to set email alerts
|

The FANCJ/MutLα interaction is required for correction of the cross-link response in FA-J cells

Abstract: FANCJ also called BACH1/BRIP1 was first linked to hereditary breast cancer through its direct interaction with BRCA1. FANCJ was also recently identified as a Fanconi anemia (FA) gene product, establishing FANCJ as an essential tumor suppressor. Similar to other FA cells, FANCJ-null (FA-J) cells accumulate 4N DNA content in response to DNA interstrand crosslinks (ICLs). This accumulation is corrected by reintroduction of wild-type FANCJ. Here, we show that FANCJ interacts with the mismatch repair complex MutLa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
227
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(245 citation statements)
references
References 48 publications
17
227
0
1
Order By: Relevance
“…YT103 and YT102M cells displayed increased resistance to MMS in comparison to YT102, as reported earlier (Kaina et al, 1991;Glaab et al, 1998). YT102 cells were quite resistant to ACNU as expected (Peng et al, 2007; -methylguanine-DNA methyltransferase (MGMT) and mismatch repair (MMR) proteins in YT102, YT103, KH101 and YT102M cell lines. The MGMT and MMR proteins were detected with immunoblotting using specific antibodies.…”
Section: Isolation Of Mutant Cells Defective In Osupporting
confidence: 81%
See 1 more Smart Citation
“…YT103 and YT102M cells displayed increased resistance to MMS in comparison to YT102, as reported earlier (Kaina et al, 1991;Glaab et al, 1998). YT102 cells were quite resistant to ACNU as expected (Peng et al, 2007; -methylguanine-DNA methyltransferase (MGMT) and mismatch repair (MMR) proteins in YT102, YT103, KH101 and YT102M cell lines. The MGMT and MMR proteins were detected with immunoblotting using specific antibodies.…”
Section: Isolation Of Mutant Cells Defective In Osupporting
confidence: 81%
“…The MMR protein-dependent release of cytochrome c from mitochondria and activation of caspases, which are hallmarks for apoptosis, also occur in the case of O 6 -methylguanine-induced apoptosis (Ochs and Kaina, 2000;Takagi et al, 2003;Hickman and Samson, 2004). As apoptosis caused by bulky DNA lesions that block DNA replication occurs even in cells deficient in MMR proteins (Peng et al, 2007;Sanada et al, 2007), the apoptosis pathway induced by O 6 -methylguanine, which does not block DNA replication, appears to be distinct from the former. It is highly likely that other proteins are also involved in the pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Because Western blot analysis demonstrated that GFP-tagged FANCJ-R251C and -Q255H were expressed similar to FANCJ-WT, we wanted to determine whether the FANCJ-R251C and -Q255H variants were associated with proteins known to interact with endogenous wildtype FANCJ. Co-immunoprecipitation experiments using nuclear extracts from HeLa cells demonstrated that TopBP1, MLH1, and BRCA1 proteins previously shown to interact with FANCJ (17,31,34) were pulled down by a GFP antibody from lysates of cells that expressed GFP-tagged FANCJ (wild-type and mutants) but not GFP alone (Fig. 9D), suggesting that FANCJ-R251C and -Q255H interact with their protein partners in a manner similar to FANCJ-WT.…”
Section: Both Fancj-r251c and Fancj-q255h Mutants Exert A Dominant Nementioning
confidence: 84%
“…Msh2 localizes to recombination intermediates in vivo (62), and subsequent heteroduplex rejection during single-strand annealing requires the Sgs1 helicase and Msh2-Msh6 (30). Moreover, the human RecQ family helicases BLM and WRN (63,64) and FANCJ helicase (65) physically and functionally interact with the MMR-components. And a single G/T mismatch located ahead of the fork junction increased the efficiency of the hMSH2-hMSH6-dependent unwinding by WRN helicase (63).…”
Section: Discussionmentioning
confidence: 99%